2013
DOI: 10.1080/2156857x.2013.801879
|View full text |Cite
|
Sign up to set email alerts
|

Survival strategies in social work: a study of how coping strategies affect service quality, professionalism and employee health

Abstract: The restructuring of human service organisations into more lean organisations has brought increased work demands for many human service professions. Social work stands out as a particularly exposed occupational group, in which high work demands are paired with a large individual responsibility to carry out the job. The objectives of the study were to identify what kind of coping strategies social workers employ to handle the imbalance between demands and resources in work and to investigate how different strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
0
29
0
3
Order By: Relevance
“…These factors have emerged in many international and domestic studies on work-related well-being among social workers (e.g. Meeuwisse et al 2011;Blomberg et al 2014;Astvik et al 2014;Karpetis 2014). In Finland, a recent report revealed that nearly 90 per cent of Finnish child welfare workers considered that statuto-39 ry child welfare services had insufficient resources.…”
Section: Work-related Well-being In the Context Of Cost Containmentmentioning
confidence: 99%
See 3 more Smart Citations
“…These factors have emerged in many international and domestic studies on work-related well-being among social workers (e.g. Meeuwisse et al 2011;Blomberg et al 2014;Astvik et al 2014;Karpetis 2014). In Finland, a recent report revealed that nearly 90 per cent of Finnish child welfare workers considered that statuto-39 ry child welfare services had insufficient resources.…”
Section: Work-related Well-being In the Context Of Cost Containmentmentioning
confidence: 99%
“…Naturally, social workers also work in order to enhance their own well-being, but they also work in order to enhance the well-being of their clients. These aims are not, however, easy to achieve or to combine (see Astvik et al 2014). Thus, it is not surprising that the work-related well-being of professional social workers or, more to the point, problems related to their well-being have become a popular topic of study during the last decades.…”
Section: On Studying Working Life and Well-being In Social Work Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…When talking about responsibility in social work, it is predominantly this moral or value-based responsibility that is in focus. Most of these studies concern the content of such moral responsibility (e.g., Payne 1999;Kleppe, Heggen, and Engebretsen 2015) or how professionals cope with competing organizational and moral responsibilities (e.g., Astvik, Melin, and Allvin 2013;McAuliffe and Sudbery 2005;Kjørstad 2005), with only a few addressing the distribution of responsibility (Solbrekke and Karseth 2006; Kleppe and Engebretsen 2010). Overall, these studies tend (implicitly) to place moral responsibility with the individual professional, overlooking the fact that social workers are not autonomous agents, able to act independently of the organizational context in which they are located (Payne 1999;Lonne, McDonald, and Fox 2004;Preston-Shoot 2011).…”
Section: Previous Work On the Distribution Of Responsibility In Publimentioning
confidence: 99%